A compact triple-band microwave filter using symmetrically placed stub-loaded open-loop resonators. Issue 3 (3rd July 2018) - Ranjan, Prashant; Tripathi, V. S.
ABSTRACT: In this paper, symmetrically placed stub-loaded open-loop resonators with magnetic coupling are used to design compact triple-band band pass filter (BPF) with improved insertion loss at passbands. Three bands of the proposed triple-band stub-loaded open-loop resonator filter are achieved by tuning length and position of open shunt stub which is connected with open-loop resonators. A lossless transmission line model is used to calculate the resonator properties. Theoretical design procedures are verified with an example of triple-band BPF design. Three passbands at 2.85, 5.9 and 8.15 GHz are achieved with reduced insertion loss. The insertion loss measured at first, second and third passbands are 0.47, 0.77 and 1.41 dB, respectively. First passband 2.76–2.9 GHz is used for the airport surveillance radar system and weather monitoring system. Second frequency band 5.82–6.16 GHz is used for the intelligent transportation system and third band 8.1–8.7 GHz is useful for satellite communication.